Strength Assessment of Polypropylene Fibre Reinforced Concrete (PPFRC) - Govindasami, S; Sakthivel, P; Harish, R (International Journal of Engineering and Technology, 2018)
In this study, the strength performance of concrete with polypropylene (PP) fibre is studied.Â  For this purpose, polypropylene (PP) fibre is added in varying volume fraction (Vf) of 0%, 0.5%, 1%, 1.5% and 2% of M25 grade concrete. The concrete was cast with Ordinary Portland Cement, M-Sand and blue metal, with and without fibres. There is a decrease in workability of concrete when the PP fibre Vf is increased from 0.5% to 2.0%. The compressive, flexural and split tensile strength of concrete have shown an improvement of 7.67%, 26.57% at Vf=1% and 33.61% and Vf=1.5% over conventional concrete. The optimum percentage of polypropylene is found to be 1% beyond which there is a reduction in strength.Â